Scenario planning as a strategic tool for multinational pharmaceutical companies in South Africa. - Dionisio, Sandra. (My University, 2014)
ABSTRACT The pharmaceutical industry in South Africa has been undergoing significant changes in the last few decades. The entrance of local and generic companies has affected the profitability and revenue generation of the multinational pharmaceutical companies who had, in the past, dominated this industry. The multinational companies have had to try to maintain their revenue and strive to regain the market leadership they once had. Their ability to do this successfully has been questioned, and so have the corporate strategies that these companies are implementing in the South African environment. Scenario planning has been identified as a tool that can be used by organisations to assist them in planning for events that have a likelihood of happening in the future. The purpose of this research was to ascertain the use of scenario planning by multinational pharmaceutical companies in South Africa and how this tool can assist them. A qualitative research methodology was adopted with 12 in depth interviews of a convenience sample of senior managers in multinational, local and generic companies. The data was analysed using the deductive method. The key findings of this research indicated that firstly, the corporate strategies being implemented, especially by the multinational pharmaceutical companies, do not address the challenges that these companies have been experiencing and secondly, these companies do not incorporate scenario planning into their strategic plans, even though the interviewees employed by these companies agreed that scenario planning would benefit them. Recommendations regarding how the multinational pharmaceutical companies can improve their corporate strategies and include scenario planning into their strategic planning have been included in this report.
MBA 2013
Keywords: International business enterprises,Pharmaceutical industry,Strategic planning.